Factors affecting athletes’ motor behavior after the observation of scenes of cooperation and competition in competitive sport: the effect of sport attitude - Stefani, Elisa De; De Marco, Doriana; Gentilucci, Maurizio (Frontiers in Psychology, 2015)
Abstract Aim: This study delineated how observing sports scenes of cooperation or competition modulated an action of interaction, in expert athletes, depending on their specific sport attitude. Method: In a kinematic study, athletes were divided into two groups depending on their attitude towards teammates (cooperative or competitive). Participants observed sport scenes of cooperation and competition (basketball, soccer, water polo, volleyball, and rugby) and then they reached for, picked up, and placed an object on the hand of a conspecific (giving action). Mixed-design ANOVAs were carried out on the mean values of grasping-reaching parameters. Results: Data showed that the type of scene observed as well as the athletes’ attitude affected reach-to-grasp actions to give. In particular, the cooperative athletes were speeded during reach-to-grasp movements when they observed scenes of cooperation compared to when they observed scenes of competition. Discussion: Participants were speeded when executing a giving action after observing actions of cooperation. This occurred only when they had a cooperative attitude. A match between attitude and intended action seems to be a necessary prerequisite for observing an effect of the observed type of scene on the performed action. It is possible that the observation of scenes of competition activated motor strategies which interfered with the strategies adopted by the cooperative participants to execute a cooperative (giving) sequence.